KEMAMPUAN MENULIS TEKS PERSUASI MELALUI MEDIA GAMBAR - Choirunnisa Choirunnisa; Rustam Rustam; Priyanto Priyanto (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the ability to write persuasive texts for class VIII junior high school students through the use of image media. The instrument used in this study was a performance test of writing persuasive text. The assessment taken in writing the text is based on the structure and linguistic rules contained in the persuasion text, namely the existence of opinions or arguments, facts, and invitation sentences. Then students write persuasive texts using image media. This research is a type of descriptive research with a quantitative approach. The research data was obtained from the students' ability to write persuasive texts. The research subjects were students of class VIIIF as many as 30 students. Analysis of the data used in this study is the result of student work.The results showed that the ability to write persuasive texts using image media in every aspect got a score above the average. In the aspect of writing arguments, the score is 84, the ability to write facts is 89, and the value of the ability to write invitations is 85. The conclusions of this study indicate that the ability to write persuasive texts for class VIIIF students is in the capable category with an average score of 86. of the overall results of the assessed aspects.